Determination of photoinduced and intrinsic birefringences in PMMA/DR13 guest-host film - Dall'Agnol, Fernando Fuzinatto; Shimizu, Flavio Makoto [UNESP]; Giacometti, Jose A. [UNESP] (Elsevier B.V., 2014)
We report measurements and analysis of photoinduced birefringence (PIB) in polymeric stretched films, hence, with an intrinsic birefringence (IB) associated to the polymeric chain orientation. It was found that transmittance signal is dependent on the angle between the film stretching direction and the probe light polarization, increasing or decreasing relatively to IB signal. Theoretical analysis considered that light propagates through the film having a photoinduced and intrinsic birefringences with independent optical axes. The transmittance signal dependence on the film angle is correctly accounted and our approach could give a phenomenological elucidation to the effect known as the inverse relaxation effect. (c) 2014 Elsevier B.V. All rights reserved.